120 NHS 24 triage of the young adult with chest pain: an analysis of patient contacts in unscheduled care. Issue 12 (23rd November 2020) - Hodgins, Peter; Guthrie, Bruce; McMinn, Megan
Abstract : Aims/Objectives/Background: Use of unscheduled care is increasing worldwide. In the UK access to services for symptoms not thought to be life-threatening is through a single telephone advice and triage service (NHS 24 in Scotland). Adults under 35 account for the largest cohort contacting this service. This study aimed to examine pathways of care in this population to inform areas for improvement to the triage process. Methods/Design: A retrospective, population study using the Scotland-wide Urgent Care Data Mart (UCD) 2015 to 2017. The UCD links data between unscheduled care services to form Continuous Urgent Care Pathways (CUPs). CUPs for those aged 15–34 years, whose initial contact was with NHS 24 and with 'chest pain' recorded as the call reason. Two outcomes were examined: admission to hospital, and admission to hospital with a 'time-critical diagnosis' defined as an admission with a discharge diagnosis of a condition that required urgent treatment. Results/Conclusions: A total of 102, 822 CUPs initiated by a call to NHS24 with chest pain as the call reason in the period studied. 35.1% of calls were made by people living in the most deprived 20% of postcodes. The most common CUP pathway accounted for 37.6% and was an NHS 24 call followed by an attendance at Primary Care Out of Hours. 25.4% of calls were considered not to represent an urgent care need. The most frequent ICD-10 code was 'chest pain, unspecified', representing 7.2% of cases with an ICD-10 code, followed by 'asthma, unspecified' at 7.1%. All NHS24 dispositions were strongly associated with increased odds of admission compared to self-care advice. Home-visits were associated with the greatest odds of time-critical diagnosis. Chest pain is a symptom of concern for young people. Use of telephone triage is effective. 9060 CUPs result in a hospital admission, although many end with a non-specific diagnosis.